Crime, gender, and social order in early modern England - Walker, Garthine (Cambridge studies in early modern British history., 2003)
This is the first study of how masculinity and femininity informed criminal behaviour and the treatment of men and women before the courts of early modern England. It shows that women were not treated leniently by the courts, and casts fresh light on the complexities of everyday life.